Drag reduction of nata de coco suspensions in circular pipe flow. (April 2015) - Warashina, J; Ogata, S
Abstract: Reducing pipe friction by adding a drag-reducing agent has attracted interest as a means to reduce energy consumption. In addition to reducing drag, these agents are required to have a low environmental load and conserve natural resources. However, no drag-reducing agent currently satisfies both these conditions. We focused on nata de coco and found that the nata de coco fiber reduced drag by up to 25%. With respect to the mechanism of drag reduction by nata de coco fiber, the relationship between drag-reduction phenomena and the fiber form of nata de coco was investigated by visualization. We also found that the drag-reduction effect appeared to be due to the formation of networks of tangled fibers of nata de coco. However, drag reduction did not occur in the case in which fibers of nata de coco did not form networks.